Development and Strategy of Small Hydropower in China (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
China is endowed with rich rural hydropower. According to the latest National Rural Water Resources Survey, the technically feasible potential amounts to 128GW, mainly distributed in the central and west part of China as well as those ethic regions, which are less developed but more populated. With the support of the Chinese government’s policy of ‘Self Construction, Self Management and Self Utilization’, Small Hydropower development has been scaled up. Thanks to the Small Hydropower (SHP) development and the grid construction, nowadays about one half of the territory, one third of the counties and 300 million rural population in China have access to electricity. The practice of China to realize rural electrification through SHP has attracted the attention of the world community including the United Nations. In future, China will continue to enhance the rural hydropower development and the environmental protection under the framework of the Renewable Energy Master Plan. Its experiences and technology could be learned by other developing countries.DOI: http://dx.doi.org/10.3126/hn.v9i0.7063 Hydro Nepal Vol.9 July 2011 12-14